Network Pharmacology and Molecular Docking-Based Study on The Anti- Inflammatory and Antioxidant Mechanisms of Morindolide - Zulkipli, Muhammad Amal; Zakaria, Yuslina; Anouar, Elhassane; Hasan, Mizaton Hazizul (International Journal of Human and Health Sciences (IJHHS), 2025)
Objective: Inflammation-related disorders, which cause much worldwide mortality, can be mitigated using network pharmacology. Network pharmacology may facilitate targeted therapy design and improve therapeutic results by finding drug- target interactions and signalling pathways. Previous studies suggest morindolide has anti-inflammatory and antioxidant properties. Thus, this study used network pharmacology and molecular docking to identify the mechanisms of these effects. Methods: Morindolide’s target genes were identified using SymMap, Swiss Target Prediction and PharmMapper databases. Anti-inflammatory and antioxidant-related genes were retrieved from the GeneCards database. Common targets were identified through Venn analysis. A protein-protein interaction (PPI) network was constructed using STRING and Cytoscape to identify hub genes. GO function and KEGG pathway analyses were performed using DAVID and ShinyGO. Molecular docking between morindolide and hub proteins was conducted using AutoDock and visualised with LigPlot. Results: The analysis revealed 56 common targets between morindolide and antiinflammatory/ antioxidant effects. Seven hub genes were identified as PTGS2, IL1B, MMP2, HSP90AA1, NOS2, PLA2GA and CYP2E1. GO analysis showed morindolide’s involvement in inflammatory response, nitric oxide biosynthesis and response to lipopolysaccharide. KEGG analysis highlighted pathways in cancer, arachidonic acid metabolism, IL-17 signalling and neurodegeneration. Molecular docking confirmed stable binding between morindolide and hub proteins, with binding energies ranging from -5.19 to -6.62 kcal/mol. The strongest interactions were observed with CYP2E1 (-6.62 kcal/mol), MMP2 (-6.6 kcal/mol) and NOS2 (-6.24 kcal/ mol). Conclusion: This study utilised network pharmacology and molecular docking to predict the potential targets, biological processes and signalling pathways involved in morindolide’s antiinflammatory and antioxidant effects, providing a theoretical foundation for future experimental research and potential clinical applications of morindolide. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S27